Comparison of the In Vitro Activity of the Glycylcycline Tigecycline (Formerly GAR-936) with Those of Tetracycline, Minocycline, and Doxycycline against Isolates of Nontuberculous Mycobacteria - Wallace, Jr., Richard J. (American Society for Microbiology, 2002)
We compared the in vitro activity of the glycylcycline tigecycline (formerly GAR-936) with those of tetracycline, doxycycline, and minocycline by broth microdilution against 76 isolates belonging to seven species of rapidly growing mycobacteria (RGM) and 45 isolates belonging to five species of slowly growing nontuberculous mycobacteria (NTM). By using a resistance breakpoint of >4 μg/ml for tigecycline and >8 μg/ml for tetracycline, all RGM were highly susceptible to tigecycline, with inhibition of 50% of isolates at ≤0.12 μg/ml and inhibition of 90% of isolates at 0.25 μg/ml for Mycobacterium abscessus and inhibition of both 50 and 90% of isolates at ≤0.12 μg/ml for M. chelonae and the M. fortuitum group. The MICs of tigecycline were the same for tetracycline-resistant and -susceptible strains, and RGM isolates were 4- to 11-fold more susceptible to tigecycline than to the tetracyclines. In contrast, no slowly growing NTM were susceptible to tigecycline, and isolates of M. marinum and M. kansasii were less susceptible to this agent than to minocycline. This new antimicrobial offers exciting therapeutic potential for the RGM, especially for isolates of the M. chelonae-M. abscessus group, against which the activities of the currently available drugs are limited.